Discovery of 3, 4-dihydropyrimido[4, 5-d]pyrimidin-2(1H)-one and 3, 4-dihydropyrido[2, 3-d]pyrimidin-2(1H)-one derivatives as novel ENPP1 inhibitors. (1st November 2022) - Jung, Jae Eun; Jang, Yunseong; Jeong, Hee Jin; Kim, Sung Joon; Park, Kichul; Oh, Do Hee; Yu, Ahran; Park, Chan Sun; Han, Seo-Jung
Graphical abstract: Abstract: Ectonucleotide pyrophosphatase/phosphodiesterase-1 (ENPP1) negatively regulates the anti-cancer Stimulator of Interferon Genes (STING) pathway. We discovered that 3, 4-dihydropyrimido[4, 5- d ]pyrimidin-2(1 H )-one and 3, 4-dihydropyrido[2, 3- d ]pyrimidin-2(1 H )-one derivatives possessed inhibitory activities on ENPP1. A structure–activity relationship (SAR) study led to the identification of 46 and 23 as potent ENPP1 inhibitors. Also, compounds 46 and 23 possessed high microsomal stabilities in human, rat, and mouse liver microsome. Additionally, CYPs (1A2, 2C9, 2C19, 2D6, and 3A4) were not inhibited by 46 and 23 . Molecular dynamics simulations provided an insight of binding modes between ENPP1 and compounds (46 and 23 ).